JNK1 Deficient Insulin-Producing Cells Are Protected against Interleukin-1β-Induced Apoptosis Associated with Abrogated Myc Expression - Michala Prause; Christopher Michael Mayer; Caroline Brorsson; Klaus Stensgaard Frederiksen; Nils Billestrup; Joachim Størling; Thomas Mandrup-Poulsen (Journal of Diabetes Research)
The relative contributions of the JNK subtypes in inflammatory β-cell failure and apoptosis are unclear. The JNK protein family consists of JNK1, JNK2, and JNK3 subtypes, encompassing many different isoforms. INS-1 cells express JNK1α1, JNK1α2, JNK1β1, JNK1β2, JNK2α1, JNK2α2, JNK3α1, and JNK3α2 mRNA isoform transcripts translating into 46 and 54 kDa isoform JNK proteins. Utilizing Lentiviral mediated expression of shRNAs against JNK1, JNK2, or JNK3 in insulin-producing INS-1 cells, we investigated the role of individual JNK subtypes in IL-1β-induced β-cell apoptosis. JNK1 knockdown prevented IL-1β-induced INS-1 cell apoptosis associated with decreased 46 kDa isoform JNK protein phosphorylation and attenuated Myc expression. Transient knockdown of Myc also prevented IL-1β-induced apoptosis as well as caspase 3 cleavage. JNK2 shRNA potentiated IL-1β-induced apoptosis and caspase 3 cleavage, whereas JNK3 shRNA did not affect IL-1β-induced β-cell death compared to nonsense shRNA expressing INS-1 cells. In conclusion, JNK1 mediates INS-1 cell death associated with increased Myc expression. These findings underline the importance of differentiated targeting of JNK subtypes in the development of inflammatory β-cell failure and destruction.